Behavior analysis of MSMEs in Indonesia using fintech lending comparative study between sharia fintech lending and conventional fintech lending - Nurbaiti, Nurbaiti; Asmuni, Asmuni; Soemitra, Andri; Imsar, Imsar; Aisyah, Siti (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
The presence of sharia financial technology (fintech) as a credible financial institution is expected to be able to help the problems that are often faced by Micro, Small and Medium Enterprises (MSMEs) in Indonesia. This study aims to determine whether there are differences in the behavior of MSME actors in the use of sharia fintech lending and conventional fintech lending. The research method used in this research is normative legal research by analyzing the laws and regulations as well as relevant studies through the issues in the study. This study uses a statutory and conceptual approach, both of which function to analyze the applicable legal rules so that differences can be found between conventional and sharia peer to peer lending fintechs and the extent to which sharia rules are applied in these fintechs. This study concludes that Islamic fintech plays a role as a driving factor in increasing the inclusiveness of Micro, Small and Medium Enterprises (MSMEs) in Indonesia. The presence of the sharia fintech industry can overcome the problems of Micro, Small and Medium Enterprises (MSMEs) in Indonesia, especially related to financing needs, ease of transaction processing, expansion of market access, and ease of preparation of financial reports.